Serum ANGPTL4 and SIRT1 factor levels and the Carotid Atherosclerotic plaque stability relationship analysis: Relationship between ANGPTL4, SIRT1 and Carotid Atherosclerotic plaque - Chen, Juhai; Li, Jiajing; Wang, Yiyi; Zhang, Zhemei; Yang, Hui; Li, Zhonglian; Wang, Tianhui; Peng, Tiecheng; Mo, Xiangang; Xu, Fengyan (Cellular and Molecular Biology, 2023)
This study was to investigate the relationship between the levels of Angiopoietin-Like Protein 4 (ANGPTL4) and Silent Mating-type Information Regulation 2 Homolog 1 (SIRT1) and the stability of carotid atherosclerotic plaque. For this purpose, 108 patients with coronary heart disease in our hospital from Jan 2021 to May 2022 were selected as the coronary heart disease (CHD) group and 80 patients with the healthy examination as the control group. Patients’ serum levels of ANGPTL4 and SIRT1 were collected, and their stability of carotid atherosclerotic plaque was determined by carotid ultrasound. According to their stability results, patients were divided into three subgroups: No plaque, Stable plaque, and Unstable plaque. The serum ANGPTL4 and SIRT1 levels were analyzed in different groups, and the correlation between their serum levels and the stability of carotid atherosclerotic plaque was analyzed by rank correlation. Results showed that the CHD group’s serum ANGPTL4 and SIRT1 levels were lower, with statistical significance (P<0.05); A statistically significant difference in serum ANGPTL4 and SIRT1 levels were observed among patients with No plaques, Stable plaques, and Unstable plaques (P<0.05); A negative correlation was observed between serum levels of ANGPTL4 and SIRT1 and the stability of carotid atherosclerotic plaque (r=-0.438, -0.717, P<0.001); Serum ANGPTL4 and SIRT1 can be used as the evaluation method of carotid atherosclerotic plaque stability. When ANGPTL4 ≤ 30.17mg/L and SIRT1 ≤ 6.91μg/L, patients were more likely to develop unstable plaques; When ANGPTL4 ≤ 30.40mg/L and SIRT1 ≤ 6.87μg/L, patients were more likely to develop plaques (instability and/or stability). In conclusion, the serum levels of ANGPTL4 and SIRT1 in patients with CHD decreased. ANGPTL4 and SIRT1 will participate in the formation and development of carotid plaque, which can be used as a serological evaluation index to evaluate the occurrence and carotid atherosclerotic plaque’s stability.